International Law Protection of Space Environment (Summary) - A. V. Kukushkina (Московский журнал международного права, 2013)
Outer space activity is a human effort that destabilizes Earth’s environment. Finding solutions to applied problems with the help of space technologies was the main reason for using the near-earth environment. Operating missile engines emit large amounts of different chemical substances into the nearearth space and the key challenge of environmental safety is to maintain the NESE natural properties and functional features.